2011
DOI: 10.1007/s10342-011-0557-6
|View full text |Cite
|
Sign up to set email alerts
|

Valuing acorn dispersal and resprouting capacity ecological functions to ensure Mediterranean forest resilience after fire

Abstract: Ecological processes within forests provide vital ecosystem services to society, most of which depend on the persistence of tree cover that can be altered after the impact of a disturbance. The aim of the present study was to examine the role of seed dispersal and resprouting that mediate resilience to large fires and evaluate the economic costs that these ecological functions provide. We used field data from 412 plots of the Spanish National Forest Inventory providing information on pre-and post-fire conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Advancing knowledge of the ecological factors driving tree-species diversification in Mediterranean forest stands is of major interest, due to the particular vulnerability of this bioclimatic region to the effects of global change (Lindner et al, 2010). In the particular case of black pine-dominated forests, for example, the occurrence of natural diversification processes allowing resprouting species such as oaks to establish in the pine understory is reportedly essential for rapid vegetation recovery after the occurrence of large wildfires (Puerta-Piñero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Advancing knowledge of the ecological factors driving tree-species diversification in Mediterranean forest stands is of major interest, due to the particular vulnerability of this bioclimatic region to the effects of global change (Lindner et al, 2010). In the particular case of black pine-dominated forests, for example, the occurrence of natural diversification processes allowing resprouting species such as oaks to establish in the pine understory is reportedly essential for rapid vegetation recovery after the occurrence of large wildfires (Puerta-Piñero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The oak stumps reflect past coppice management for charcoal and firewood. The European jay (Garrulus glandarius) disperses acorns into pine stands from old isolated trees growing in nearby fields (Puerta-Pinero et al 2012). The presence of these oaks increases the present adaptability of these forests to fire, because unlike pines, oaks are able to resprout and rapidly establish ground cover and a tree overstory after fires (Rodrigo et al 2004).…”
Section: Memorymentioning
confidence: 99%
“…Mixed pine-hardwood forests are expected to be more resilient to disturbances than monospecific pine stands (Jactel et al 2009;Vallejo et al 2006), particularly to allow quicker vegetation recovery after frequent large fires (Puerta-Piñero et al 2012). Favoring the establishment of resprouting hardwood seedlings under Aleppo pine stands is thus recommended, but no clear management methods have yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, hardwood species are mostly resprouters: they have the ability to regrow from dormant buds and belowground reserves after a fire, which promotes faster vegetation recovery and makes them less vulnerable to high fire frequencies (Pausas et al 2004;Schelhaas et al 2010). Resprouter species can thus be considered keystone species for fire-resilient forests (Puerta-Piñero et al 2012). Furthermore, monospecific Aleppo pine stands have been shown to be highly sensitive to insect attacks (Maestre and Cortina 2004) and to reduce plant species richness and diversity in the understory (Chirino et al 2006), whereas mixed pine-hardwood stands are shown to be less sensitive to pest outbreaks and herbivory (Jactel and Brockerhoff 2007), to potentially host greater biodiversity (Cavard et al 2011), and to be more resilient to disturbances and changing environmental conditions for a number of ecosystem processes (Jactel et al 2009;Yachi and Loreau 1999).…”
Section: Introductionmentioning
confidence: 99%